Green Infrastructure for Urban Flooding: Knowledge Domains and Research Evolution (2015–2024) - Jin-Pyo Kim; Jin-Oh Kim (Land)
Urban flooding represents a critical socio-ecological challenge exacerbated by climate change and rapid urbanization, with green infrastructure (GI) emerging as a transformative approach to flood management. This study employs an innovative methodological framework integrating the Biblioshiny, CiteSpace, and Orange3 analytical tools to examine research trends and evolutions in GI for urban flooding from 2015 to 2024. The bibliometric analysis of 813 publications reveals a profound epistemological transition from technically oriented approaches toward integrated socio-ecological frameworks. The citation patterns demonstrate increasing scholarly attention on multifunctionality, climate resilience, and governance dimensions, with the United States and China emerging as dominant research hubs. The analysis identifies distinct thematic clusters reflecting the field’s intellectual progression from hydrological engineering paradigms toward systemic conceptualizations that recognize the complex interactions between technical, ecological, and social dimensions. Despite these advancements, persistent knowledge gaps remain regarding longitudinal performance evaluations, governance frameworks for maintenance, and scalar integration from site-specific interventions to watershed-level outcomes. These findings emphasize the need for methodological innovation addressing the temporal dimensions of GI performance and institutional arrangements for its implementation across diverse urban contexts, positioning GI as a critical component of sustainable urban water management amid increasing climatic uncertainty.